De Leste a Oeste: Representações da Rússia no audiovisual dos Estados Unidos (1939-2022) - Franco, João Vitor Pires (2024)
This study examines the representation of Russia and its citizens in American audiovisual productions, with a particular focus on the persistence of negative stereotypes in the post-Cold War era. By analyzing a wide range of films and series, from classics like Ninotchka (1939) and From Russia with Love (1963) to contemporary productions such as Lord of War (2005), Chernobyl (2019), and Stranger Things (2022), this research seeks to identify the evolution of these representations and the influence of political factors in this process. The study investigates the presence of Russophobic elements, the relationship between major Hollywood studios such as Warner, Fox Pictures, MGM, and Paramount, and US security agencies like the CIA and the Department of Defense, and the role of cinema in constructing alternative narratives about international reality. By analyzing selected works, this study aims to understand how these productions shape public perception of Russia, both in the United States and globally, given the distribution power of the American audiovisual industry. The relevance of this research lies in understanding how audiovisual media, as a powerful means of communication and aesthetic element, influences international relations. By connecting the analysis of films and series with International Relations Theories, this study seeks to demonstrate how the popular and the political intertwine in the construction of cultural and political meanings.